A General Review of the Role of Technology in the English Language Learning Processes - Rojas, Arnold Yesid; Novoa, Luis Alejandro; Sandoval, Santiago Andrés (Universidad Pedagógica y Tecnológica de Colombia, 2020)
This article aimed at presenting general trends regarding the role of technology in the English language learning process. The benefits of using technology in the process of learning English, as well as the importance of using technology as a method to teach a foreign language, will be discussed. This study discusses the use of technology as a way to promote teaching English as a foreign language, as well as how it can transform the teaching and learning process.